Mechanism of bactericidal efficacy against nosocomial pathogenic Staphylococcus aureus strain caused by fatty acids from Hermetia illucens larvae fat - Heakal Mohamed; Elena Marusich; Margarita Pustovalova; Sergey Leonov (Scientific Reports)
Abstract Hermetia illucens (HI) is a promising insect that widely employed as a sustainable source of food and has been recently used as a successful antimicrobial agent. Fatty acids extracted sequentially from HI larvae fight against MDR nosocomial pathogenic bacteria such as Staphylococcus aureus. This strain is resistant to various antibiotics, causing many issues and deaths in healthcare sectors. The present study aimed to elucidate the mechanism of bactericidal efficacy of fatty acids (FAs) in HI larvae fat against S. aureus ATCC 55804 strain. The disk diffusion assay, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and half of the minimum inhibitory concentration (MIC50) applied in this study, proved the antimicrobial activity of fatty acids. The mechanism of FAs action was evaluated by several approaches, including inhibition of the bacterial growth curves and salt tolerance assays, scanning electron (SEM) and transmission electron (TEM) microscopies. S. aureus ATCC 55804 was resistant to 30% out of ten tested antibiotics belonging to different classes. In addition, microscopic observations showed the inhibitory effect of acidic water methanol extract (AWME3) by targeting of the S. aureus ATCC 55804 cell membrane and causing the considerable morphological alterations on the bacterial wall and destruction its cytoplasmic contents leading to the cellular content release and cell death. This study revealed the potential efficacy of AWME3 as a novel therapeutic antibacterial agent effective against resistant nosocomial bacterial pathogens.